Synthesis and characterization of a recyclable graphene oxide-surface- engineered copper(II) Schiff base complex: Catalytic application in synthesis of 1, 2, 3-triazoles and 2H-indazoles. Issue 4 (August 2021) - Kumar, Akash; Verma, Shruti; Pathak, Devendra Deo
Abstract: A new graphene oxide (GO) supported Cu(II) Schiff base complex (GO-SB-Cu) has been synthesized by utilizing Schiff base functionalized GO (GO-SB) and copper acetate in ethanol under reflux. The synthesized complex was characterized using several techniques such as Fourier Transform Infrared spectroscopy (FTIR), Powdered X-ray Diffraction (PXRD), Fourier Transform (FT-Raman), Thermo Gravimetric Analysis (TGA), Field Emission Scanning Electron Microscopy (FESEM), High Resolution Transition Electron Microscopy (HRTEM), Elemental Dispersive X-ray analysis (EDX), Elemental mapping, X-ray Photo electron Spectroscopy (XPS) and Atomic Absorption Spectroscopy (AAS) analysis. The complex was found to be highly efficient in the click reaction for synthesis of 1, 4-disubstituted 1, 2, 3-triazoles at room temperature and an operationally simple and efficient one-pot synthesis of 2 H -indazoles from commercially accessible reactants at ambient temperature, without using any base, additive or co-catalyst. A variety of electron donating/withdrawing groups were employed to explore the scope of the reactions. Interestingly, aliphatic and heterocyclic amines were also tested and found active in the synthesis of 2 H -indazoles. Our results demonstrated that the reaction could be scaled up conveniently and the catalyst could be easily recycled upto successive four times without any noteworthy loss in the catalytic action. High yield of the products, easy workup, environmentally benign, high stability of the catalyst and mild reaction conditions are the key points of this catalyst. All the synthesized organic products were identified by 1 H and 13 C NMR spectroscopy. Graphical Abstract: ga1 Highlights: Synthesis and characterization of graphene oxide-surface-engineered Cu(II) Schiff base complex, GO-SB-Cu. Applications of GO-SB-Cu as an efficient heterogeneous catalyst for synthesis of 1, 2, 3-triazoles and 2 H -indazoles. The catalyst can be easily recovered from the reaction mixture by simple filtration. The catalyst could be recycled up to four times.